2011
DOI: 10.1152/jn.00717.2010
|View full text |Cite
|
Sign up to set email alerts
|

Parasagittally aligned, mGluR1-dependent patches are evoked at long latencies by parallel fiber stimulation in the mouse cerebellar cortex in vivo

Abstract: Wang X, Chen G, Gao W, Ebner TJ. Parasagittally aligned, mGluR 1 -dependent patches are evoked at long latencies by parallel fiber stimulation in the mouse cerebellar cortex in vivo. J Neurophysiol 105: 1732-1746, 2011. First published February 2, 2011 doi:10.1152/jn.00717.2010.-The parallel fibers (PFs) in the cerebellar cortex extend several millimeters along a folium in the mediolateral direction. The PFs are orthogonal to and cross several parasagittal zones defined by the olivocerebellar and corticonucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
71
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(73 citation statements)
references
References 107 publications
2
71
0
Order By: Relevance
“…Although intensively studied, previous work has focused on the charaterization and possible role of SS pauses, with limited interest in the cerebellar cortical location of the studied PCs (Kim et al 2012;Sugihara and Quy 2007;Wadiche and Jahr 2005;Wang et al 2011;Xiao et al 2014;Zhou et al 2014). In the current study, we systemically correlated the locations of PCs with the occurrence of long pauses and found that these cells are often located close to the exposed brain surface, near the craniotomy.…”
Section: Methodological Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although intensively studied, previous work has focused on the charaterization and possible role of SS pauses, with limited interest in the cerebellar cortical location of the studied PCs (Kim et al 2012;Sugihara and Quy 2007;Wadiche and Jahr 2005;Wang et al 2011;Xiao et al 2014;Zhou et al 2014). In the current study, we systemically correlated the locations of PCs with the occurrence of long pauses and found that these cells are often located close to the exposed brain surface, near the craniotomy.…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…PCs that have a similar zebrin "identity," i.e., have a similar expression level of zebrin II (from here on: zebrin), typically receive inputs from the same part of the inferior olive, and project their axons to the same part of the cerebellar nuclei (Apps and Hawkes 2009;Brochu et al 1990;Pijpers et al 2006;Sugihara 2011;Sugihara and Quy 2007;Voogd and Ruigrok 2004), creating functional units, or modules. More recently physiological differences between modules have been described in terms of plasticity (Wadiche and Jahr 2005;Wang et al 2011) and firing dynamics and rates (Kim et al 2012;Xiao et al 2014;Zhou et al 2014). In addition, the cerebellar cortex can also be subdivided in zones on the basis of development and function by borders that run perpendicular to the sagittal bands, i.e., into transverse zones (Ozol et al 1999;Reeber et al 2013).…”
mentioning
confidence: 99%
“…Although the function of aldolase C/zebrin II in the cerebellum is still largely unclear, other physiologically important molecules (e.g., mGluR1b, phospholipase C␤3/4, protein kinase C␦, and glutamate transporter EAAT4) in PCs are known to exhibit the same or complementary stripe-shaped expression patterns as aldolase C (Chen and Hillman, 1993;Sarna et al, 2006;Paukert et al, 2010;Wang et al, 2011). Thus aldolase C compartmentalization is of the same functional importance as above molecules in the cerebellar cortex.…”
Section: Visualization Of Cerebellar Zones In Live Micementioning
confidence: 99%
“…Thus aldolase C compartmentalization is of the same functional importance as above molecules in the cerebellar cortex. Indeed, a recent study has shown that firing properties of PCs depend on the expression of aldolase C (Zhou et al, 2014). These previous studies required post hoc anatomical identification of aldolase C compartments in perfused brain sections.…”
Section: Visualization Of Cerebellar Zones In Live Micementioning
confidence: 99%
See 1 more Smart Citation